2003
DOI: 10.1046/j.1096-3642.2003.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Hexacorallia (Cnidaria: Anthozoa)

Abstract: The composition of and relationships among higher-level groups within the anthozoan subclass Hexacorallia ( = Zoantharia) has been controversial because independent analyses of anatomy, life history, ultrastructure, and molecular sequences have failed to provide a consistent framework for drawing taxonomic boundaries or understanding phylogenetic relationships. The relationship among stony corals (order Scleractinia), sea anemones (order Actiniaria), and corallimorpharians (order Corallimorpharia) has been par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
123
3
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 84 publications
(127 reference statements)
11
123
3
5
Order By: Relevance
“…Thus, the scleractinian skeleton has likely not been as evolutionarily ephemeral (8) as some have suggested (9). Nevertheless, molecular data have consistently confirmed the close relationship between Scleractinia and nonskeletonized Corallimorpharia (8,12,14,15) evident from morphology. However, up to this point, molecular analyses have failed to provide resolution or a consistent signal at the base of the clade uniting Scleractinia and Corallimorpharia.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, the scleractinian skeleton has likely not been as evolutionarily ephemeral (8) as some have suggested (9). Nevertheless, molecular data have consistently confirmed the close relationship between Scleractinia and nonskeletonized Corallimorpharia (8,12,14,15) evident from morphology. However, up to this point, molecular analyses have failed to provide resolution or a consistent signal at the base of the clade uniting Scleractinia and Corallimorpharia.…”
mentioning
confidence: 82%
“…Similarity in scleractinian and corallimorpharian cnidoms also has been used to argue that scleractinians have an especially close relationship to Corallimorpharia (6,7). The cladistic analysis of Daly et al (8) also identified sperm ultrastructure characteristics that may be synapomorphies for the clade uniting Scleractinia and Corallimorpharia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stony corals belonging to the order Scleractinia (Anthozoa: Hexacorallia) are a clade of cnidarians that build a calcium carbonate skeleton in the form of aragonite, and are sister group to the non-stony corallimorpharians (Daly et al 2003;Fukami et al 2008;Kitahara et al 2014;Lin et al 2014). At present, Scleractinia contains 31 families, about 240 genera, and over 1,500 species (Cairns 1999(Cairns , 2009Appeltans et al 2012;Huang and Roy 2015), including both zooxanthellate-hosting the symbiotic dinoflagallate Symbiodiniumand azooxanthellate corals.…”
Section: Introductionmentioning
confidence: 99%
“…This group of corals lacks calcareous skeleton (den Hartog 1980;Daly et al 2003Daly et al , 2007Fautin et al 2007) and can be found either as solitary polyps (den Hartog 1980) or as colonies that cover extensive sections of a reef (Gerald and Roger 1994;Muhando et al 2002). According to Daly et al (2007), the order Corallimorpharia includes four families (Corallimorphidae, Discosomatidae, Ricordeidae, and Sideractiidae), nine genera (12 genera according to Fautin et al 2007), and at least 24 valid species.…”
Section: Introductionmentioning
confidence: 99%